Axon-glia interaction and membrane traffic in myelin formation - White, Robin; Krämer-Albers, Eva-Maria (Frontiers in Cellular Neuroscience, 2014)
In vertebrate nervous systems myelination of neuronal axons has evolved to increase conduction velocity of electrical impulses with minimal space and energy requirements. Myelin is formed by specialised glial cells which ensheath axons with a lipid-rich insulating membrane. Myelination is a multi-step process initiated by axon-glia recognition triggering glial polarisation followed by targeted myelin membrane expansion and compaction. Thereby, a myelin sheath of complex subdomain structure is established. Continuous communication between neurons and glial cells is essential for myelin maintenance and axonal integrity. A diverse group of diseases, from multiple sclerosis to schizophrenia, have been linked to malfunction of myelinating cells reflecting the physiological importance of the axon-glial unit. This review describes the mechanisms of axonal signal integration by oligodendrocytes emphasising the central role of the Src-family kinase Fyn during CNS myelination. Furthermore, we discuss myelin membrane trafficking with particular focus on endocytic recycling and the control of PLP (proteolipid protein) transport by SNARE proteins. Finally, PLP mistrafficking is considered in the context of myelin diseases.